Editorial - Knights, Francis (Oxford University Press, London; Oxford, 2010)
RESUMEN: The subtitle of this issue reflects a happy serendipity rather than any formal theming, and were it not for one or two articles lying just outside these boundaries, it could as easily have been 'Three centuries of English music' or indeed 'Three centuries of music in London'. The broad historical range, taking us from Byrd right into the 19th century, is similarly accidental yet welcome. However, such a subtitle might also cause us to ponder what, if anything, is meant by 'Englishness' in music, especially early music. As the 2009 Proms season showed, our associations here are so intimately tied up with Elgar and Vaughan Williams (not to mention Gilbert and Sullivan) that it is hard to see what might be the role and position of a 'national' music before such composers, whose works are in some way a reflection of Victorian self-confidence and prosperity